2020
DOI: 10.47577/tssj.v9i1.928
|View full text |Cite
|
Sign up to set email alerts
|

Students` perceptions about the impact of COVID-19 on learning process. A sociological approach

Abstract: The last six months have been marked by the worldwide spread of the new coronavirus (COVID-19) which has triggered a global pandemic crisis. Thus, among the most affected fields of activity is education, educational institutions being forced to transfer all the curricular activities in the online environment, by using various digital tools and also Social Media. Due the rapidly spreading of the novel coronavirus, since the beginning of this year, thousands of higher education institutions around the world have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…Pharmacy Education 20(2) XXX -XXX results to be affected by the COVID-19 pandemic (Apostol, 2020). This study reported the same finding, where 53.3% reported that they are strongly affected, and only 5.1% of the students reported that they were not affected by the COVID-19 pandemic.…”
Section: Impact Of Covid-19 On Pharmacy Students In Sudansupporting
confidence: 65%
“…Pharmacy Education 20(2) XXX -XXX results to be affected by the COVID-19 pandemic (Apostol, 2020). This study reported the same finding, where 53.3% reported that they are strongly affected, and only 5.1% of the students reported that they were not affected by the COVID-19 pandemic.…”
Section: Impact Of Covid-19 On Pharmacy Students In Sudansupporting
confidence: 65%
“…Students can search for these courses in specialized departments at their universities, and training workshops focused on teaching these skills should be encouraged by ethnobiological professional societies. As a result of Covid‐19, many workshops and courses are now available online, increasing access to all (Apostol, 2020; Sikora et al ., 2020; Vandebroek et al ., 2020) and there are many free tutorials and code snippets available online for R and Python. Learning these techniques may require creativity but their implementation has the potential to change the course of ethnobiology.…”
Section: Discussionmentioning
confidence: 99%
“…Generally defined, online social media tools are information and communication technology platforms (Chourabi, 2012 andApostol, 2020) such as blogs, wikis, Facebook, web-based communication spaces (e.g., chat rooms), audio, photo, and video sharing, virtual worlds, Twitter, and many more. Earlier forms of internet-based interactions between government and citizens were known as e-government or Web 1.0 platforms (e.g., government websites) and only configured for one-way communications and limited forms of citizen feedback (Fan, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%